2023
DOI: 10.21203/rs.3.rs-2475564/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes Up to Age 36 Months after Congenital Zika Virus Infection – U.S. States

Abstract: Background: To characterize neurodevelopmental abnormalities in children up to 36 months of age with congenital Zika virus exposure. Methods: From the U.S. Zika Pregnancy and Infant Registry, a national surveillance system to monitor pregnancies with laboratory evidence of Zika virus infection, pregnancy outcomes and presence of Zika associated birth defects (ZBD) were reported among infants with available information. Neurologic sequelae and developmental delay were reported among children with ≥ 1 follow-u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Among pregnancies with confirmed ZIKV infection, 6.2% of infants had a ZBD. In areas with widespread local transmission of the virus, ZBDs were 9 times higher than in areas without local transmission [4][5][6] . A limitation of findings from the USZPIR is a lack of a control group of pregnant persons who were not exposed to ZIKV during pregnancy.…”
Section: Current State Of Knowledge Regarding Zika Virus Epidemiology...mentioning
confidence: 89%
See 1 more Smart Citation
“…Among pregnancies with confirmed ZIKV infection, 6.2% of infants had a ZBD. In areas with widespread local transmission of the virus, ZBDs were 9 times higher than in areas without local transmission [4][5][6] . A limitation of findings from the USZPIR is a lack of a control group of pregnant persons who were not exposed to ZIKV during pregnancy.…”
Section: Current State Of Knowledge Regarding Zika Virus Epidemiology...mentioning
confidence: 89%
“…The Zika virus (ZIKV) was brought to global attention in 2016 when scientists discovered that ZIKV infections were linked to microcephaly and Guillain-Barre syndrome (GBS) [1][2][3] . ZIKV infection during pregnancy was later appreciated to cause a range of other congenital malformations [4][5][6] . ZIKV infection is also linked to Guillain-Barré syndrome, neuropathy, and myelitis in both children and adults.…”
mentioning
confidence: 99%
“…Moreover, a cohort study from French Polynesia found that maternal ZIKV infection was not associated with an excess burden of developmental delay during early childhood [ 33 ]. Data from the U.S. Zika Pregnancy and Infant Registry show that among children with confirmed prenatal Zika-exposure but without Zika-associated birth defects, the rate of confirmed or possible NDD was 7.4% up to 36 months of age, which is considered to be within the expected general population rate [unpublished personal data] [ 34 ]. Nevertheless, developmental delays, particularly in cognitive and language domains, have been previously reported in normocephalic ZIKV-exposed children [ 34 , 35 , 36 , 37 ] and authors have cautioned against normocephaly being used as a proxy marker for reassurance of typical neurodevelopment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the U.S. Zika Pregnancy and Infant Registry show that among children with confirmed prenatal Zika-exposure but without Zika-associated birth defects, the rate of confirmed or possible NDD was 7.4% up to 36 months of age, which is considered to be within the expected general population rate [unpublished personal data] [ 34 ]. Nevertheless, developmental delays, particularly in cognitive and language domains, have been previously reported in normocephalic ZIKV-exposed children [ 34 , 35 , 36 , 37 ] and authors have cautioned against normocephaly being used as a proxy marker for reassurance of typical neurodevelopment [ 12 ]. In one Brazilian study, lower head circumference for age was found to be a predictor of neurodevelopmental delay in normocephalic ZIKV-exposed children at 6 months [ 38 ].…”
Section: Discussionmentioning
confidence: 99%